Artifical graphene lattice in 2D electron systems in GaAs/AlGaAs - Arrieta, D. I. (2013)
The graphene, since 2004, had show some exceptional mechanical, thermal and electronic properties in se- veral configurations such as optical modulators, transistors, gas detectors, electrocromic devices, electrodes, thermal dissipaters and integrated circuits. There is an inconvenient in the atom by atom manipulation for obtain the specific properties for each function in each proposed device. We account between them, the disorder in the graphene structure and the intercalation of impurities in the hexagonal structure and the imperfections of the substrate that incorporate ripples in the graphene structure. Nevertheless, these do not modify the cones of the valence and conduction bands. The Dirac point remains. Other options has been suggested to induce a gap between the K and K′ symmetry points where lay the Dirac points in which converge the two charge carrier cones, electrons and holes. One of them is to build an artificial hexagonal lattice over a two dimensional electron gas which found near to the interface of the two semiconductor material with different gaps, GaAs/AlGaAs. Therefore, the objective of the present work is to verify if the artificial hexagonal lattice simulate the electronic properties of graphene, i.e., to verify the existence of Dirac points in an artifical hexagonal lattice.